PELATIHAN K3 MADYA DENGAN STUDI KASUS LINGKUNGAN KERJA PADA PT ALL LIFTING INDONESIA KOTA BATAM - Yunesman, Yunesman; Yasra, Refdilzon (LPPM Universitas Ibnu Sina, 2026)
High-risk work environments require a robust safety system and training tailored to on-site conditions. At PT All Lifting Indonesia in Batam, various workplace hazards were identified as insufficiently managed, including the absence of designated pedestrian pathways, exposed electrical cables, and the use of unprotected equipment. This study aims to enhance workers’ understanding and skills in identifying and managing occupational risks through a contextualized intermediate-level occupational safety and health (OSH) training program based on real case studies. The method employed was a community service-based participatory approach involving direct observation, structured interviews, and on-site training activities. Risk identification was conducted using HIRADC and Job Safety Analysis (JSA) instruments. The results revealed a significant improvement in participant comprehension, with the average pre-test score rising from 56% to 84% in the post-test. Participants also demonstrated the ability to propose relevant risk control measures based on actual field conditions. Training was delivered through a combination of demonstrations, group discussions, and hands-on exercises using hazard identification tools at the worksite. Beyond improving knowledge, the program cultivated collective awareness of the importance of implementing proper safety procedures. The company responded positively and expressed commitment to integrating the training recommendations into internal policies. The findings suggest that OSH training rooted in real-world data and field-based cases is more effective in fostering safety awareness than conventional theoretical approaches, and may serve as a replicable training model for similar industrial sectors.